2008
DOI: 10.1111/j.1744-7909.2008.00394.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and Tissue Age Influences on Endophytic Fungi of Pinus tabulaeformis (Pinaceae) in the Dongling Mountains, Beijing

Abstract: Endophytic fungi associated with Pinus tabulaeformis Carr. were investigated in the Dongling Mountains of Beijing. A total of 16,200 tissue segments of P. tabulaeformis from four sample collections were processed, and 10,659 fungal isolates were recovered. The overall colonization and isolation rates of endophytic fungi from high to low were spring > winter > autumn > summer and in different tissues were bark > needle > xylem, irrespective of sampling seasons. The colonization rates of endophytic fungi of need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 115 publications
(52 citation statements)
references
References 30 publications
(46 reference statements)
4
45
0
2
Order By: Relevance
“…This is perhaps because the roots of S. grandis are perennial, while leaves are annual. This is consistent with a hypothesis of predominantly horizontal transmission of endophytes, as old plant tissues would have had more time to accumulate endophytes from the environment (Bertoni and Cabral 1988;Taylor et al 1999;Wang and Guo 2007;Guo et al 2008 ).…”
Section: Effect Of Tissue Types and Treatments On Colonization Ratesupporting
confidence: 87%
“…This is perhaps because the roots of S. grandis are perennial, while leaves are annual. This is consistent with a hypothesis of predominantly horizontal transmission of endophytes, as old plant tissues would have had more time to accumulate endophytes from the environment (Bertoni and Cabral 1988;Taylor et al 1999;Wang and Guo 2007;Guo et al 2008 ).…”
Section: Effect Of Tissue Types and Treatments On Colonization Ratesupporting
confidence: 87%
“…L. chartarum and X. feejeensis were isolated only from twigs of A. marina and B. gymnorrhiza , respectively. These results suggested that some endophytic fungi showed certain tissue preference (Guo et al 2008; Xing et al 2011; Sun et al 2012). …”
Section: Discussionmentioning
confidence: 96%
“…De Souza Sebastianes et al (2013) reported that the colonisation rate of endophytic fungi was significantly higher in branch than in leaf among three mangrove species in Brazil. The possible explanation might be that the structure and substrates are different between twig and leaf tissues, or that the twigs are more permanent than leaves, which influence the colonisation of endophytic fungi (Taylor et al 1999; Gilbert et al 2002; Wang and Guo 2007; Guo et al 2008). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This occurred despite the fact that sampling sites were located in areas subject to differing microenvironments in vivo and in vitro. In vivo microenvironment factors, in particular, have pronounced effects on endophytic microbial communities in plant systems (Guo et al 2008;Martin-Garcia et al 2011).…”
Section: Discussionmentioning
confidence: 99%